Representing Moderate Da’wah: Habib Ja’far on Deddy Corbuzier’s YouTube: Representasi Dakwah Moderat: Habib Ja’far di YouTube Deddy Corbuzier - Rofiqotudz Dzakiyah Dzakiyah; Siti Riskiyah (Alhadharah: Jurnal Ilmu Dakwah, 2026)
Digital communication has reconfigured Indonesian Islamic propagation, establishing podcasts as a dominant medium for younger Muslims. This study examines the representation of moderate dakwah by Habib Husein Ja’far Al-Hadar on Deddy Corbuzier’s YouTube channel. Utilizing qualitative content analysis frameworks from Krippendorff and Miles, Huberman, and Saldaña, the research analyzes three high-viewership videos focusing on tolerance and interreligious dialogue. Findings reveal that moderate dakwah is constructed through three operational pillars: tasamuh (tolerance), which affirms universal human values across theological differences; tawassuth (the middle way), which offers measured, character-based responses to social conflicts; and la ’anf (non-violence), which uses casual humor and culturally resonant language to dismantle intimidatory discourse. Furthermore, the study introduces the concept of “Digital-Interreligious Homophily,” arguing that moderate dakwah in new media environments relies less on formal religious authority and more on communicative parity achieved through cultural ego-reduction. While this claim is limited to textual representation and has not been tested against audience-response data, it provides a significant modification to classical persuasion communication theory as applied to contemporary Islamic digital media. KEYWORDS Islamic communication; religious moderation; digital dakwah; podcast; wasathiyyah